Learning Strategies of Distance Education Students In Managing Time for Completing Online Tutorial Assignments - Gafur, Abd; Jameel, Ami Hibatul (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
Students at Universitas Terbuka are required to manage their time effectively to complete online tutorial assignments on time. Despite their work commitments, the flexibility provided by Universitas Terbuka should enable students to fulfill their academic responsibilities. This study aims to analyze the time management strategies employed by Universitas Terbuka students in completing online tutorial assignments. The research adopts a mixed-method approach, utilizing both quantitative and qualitative methods, with data collected through surveys and interviews. The study involved 230 students from the Educational Technology Study Program at Universitas Terbuka. Data analysis was conducted using descriptive statistical analysis. The results indicate that (1) the utilization of time for completing online tutorial assignments falls into the good category, (2) discipline in submitting assignments is also categorized as good, but (3) time management for studying remains suboptimal, suggesting that students have not yet fully developed effective study time management skills.